Caracterización de valores hemáticos (biometría hemática) en la especie lama pacos (alpacas) - Sánchez Iza, Ana Elizabeth (2015)
This research is based on the characterization of hematologic values alpacas, as there is little information in Ecuador, it will be helpful to the veterinarian, the total blood cell count is determined with laboratory parameters erythrocyte, the Total white blood cell count and differentiation. A height of 3936 meters was held in the community that has Apahua Huacayas alpacas and 46 females were used 1 - 5 years old, blood samples were collected by venipuncture of peripheral vessel using vacuum tubes with EDTA. Descriptive therefore aims to present the actual values of the CBC in the blood of the alpacas through laboratory research - analytical study methodological design was used. And this data was obtained a reference for comparison of physiological parameters and determining its variation to the pathology. The analysis of the samples was performed at the Veterinary Clinic Planet Life....